Kepemimpinan Kepala Desa H. Sudiarto Bc, Hk dalam membangun Desa Sokokidul Kecamatan Kebonagung Kabupaten Demak Menuju Desa Berprestasi Tahun 2013/2014 - Nia Hapsari Putri; Ahmad Taufiq; Lusia Astrika (Journal of Politic and Government Studies, 2017)
This research discusses the leader in village The leader is essentially a person who has the ability to influence the behavior of others in his work with the use of power. Sokokidul village is one of the villages that has a leader who has the ability to successfully build the village to be developed. The research aims to explain the leadership of the village head in order to build Sokokidul village into a growing and achieving village with various potential village. Both from natural resources and human resources. The research was conducted using qualitative method. Technique of collecting data is done by interview, documentation and literature study. Validity and data reliability are tested using the source triangulation technique. The author uses the leadership and the government leader. The result show tha H. Sudiarto’s leadership is good, because he has innovations to develop the village as well as the many awards received by Sokokidul village. He can also perform his role well as; The role of generating spirit, the role of social relationships and the role of information delivery. He is also a democratic leader proven by good communication between leaders and subordinates and repect the opinions of subordinates and include subordinates of each decision-making.Key Word : Leadership, Village Head, Development